Hepatitis C: sociodemographic and clinical profile of patients treated with direct-acting antivirals in a pharmaceutical office - Karem Aline Pegoraro; Edson Luiz Folador; Dennis Armando Bertolini; Angela Maria Campagna (Universidade Estadual de Maringá, 2023)
To report the sociodemographic and clinical profile of patients treated with direct-action antivirals (DAAs). Patients infected with hepatitis C virus in current treatment were followed up in a pharmaceutical office. Sociodemographic, clinical and medicines uses characteristics were obtained. A total of 62 patients were enrolled, with a higher proportion of men, aged between 40 and 69 years, low schooling, and workers. Were predominant the HCV virus genotype 1 (45.2%) and 3 (48.4%), and 19.4% were cirrhotic. Of the referred comorbidities, stood out those diseases related to the cardiovascular system (19.8%), psychiatric disorders (17.6%), endocrine and metabolic disorders (14.5%). Co-infections represented 5.2%, and were distributed between acute hepatitis A (1.0%), chronic viral hepatitis B (2.1%), and HIV (2.1%). Previous or current use of licit / illicit substances was reported by 33.9% of patients. A significant difference was identified in the youngest age group (25 to 39 years, p = 0.02), with a lower average viral load compared to the other age groups. The pharmacotherapeutic follow-up carried out in the period resulted in 157 pharmaceutical consultations. Patients with hepatitis C using DDAs were mostly men, aged between 40 and 69 years. Type 3 HCV genotype was most frequently identified. The presence of cirrhosis and other comorbidities serves as an alert for health professionals in the implementation of public health policies.